Application of Rasch Measurement Model in Examining the Implementation of ISO 9000 Organizational Performance in Malaysia - Rohaizah, Saad (2012)
Quality Management System (QMS), especially the ISO 9000 QMS, is not a concept new to the world. Since its establishment, the ISO 9000 QMS has undergone several revisions in coping with the changes in an increasingly competitive market environment. Consequently, many studies have been conducted in view of the above. However, the consensus among the scholars regarding the effect of ISO 9000 implementation and organisational performance is still inconclusive. Issues like the level of comprehensiveness in ISO 9000 implementation, inconsistent variables, and differing methodologies might be of some major variances. In general, this study attempts to revisit these issues and analyse them using the Rasch Measurement Model. The data were collected through series of survey on randomly selected automotive-based companies determined beforehand. The survey questions were developed based on previous literature in which the Likert scale (1 – low to 5 – high) was used to measure the perception of the respondents. Working on the 28% response rate, the data was processed and analysed using Winstep 3.6 software. The results revealed that there is a positive and significant relationship between ISO 9000 implementation and organisational performance. They also revealed that the higher the capability of the organisation in implementing ISO 9000 standard requirements and guidelines, the higher the probability of success in optimising organisational performance. Fundamentally, this study seeks to contribute in view of applying a new paradigm of measurement theory in the area of quality management. Consequently, the output is expected to be of a valuable assistance for organisations in determining their capability and planning for continuous improvement in the area of quality management.